Livestock farming in Algerian semi-arid forests: the case of Boutaleb forest - Sahraoui H.; Madani T.; Kermouche F. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Agriculture and livestock breeding have always existed in the forest of Boutaleb, Northeastern Algeria. A study was carried out in 2008, and aimed to collect data on agriculture and breeding systems to set up a development project. The study involved 116 farmers and dealt with households, production units and their relationships with the forest resources. The data collected was analyzed using multiple correspondence and hierarchical clustering methods. The average seasonal grazing period of small ruminants in the forest of Boutaleb is 6 months per year. The breeding was deemed a good way to enhance and take advantage of the region’s silvopastoral resources. The typology has distinguished four farming systems: (1) Small and very extensive, (2) Small and moderately supported, (3) Medium-size and supported, (4) Large and relatively intensive. In addition, the study showed that 97% of farms are family-run and reserve 96% of their agricultural area for wheat and barley production for human and animal consumption to compensate for the lack of silvopastoral resources during the lean season. Subsequently, proposals to protect the environment and promote the synergy between silvopastoral resources and ruminant breeding were recommended.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)